Summary of the 11th International Conference on Human Herpesviruses‐6A, ‐6B, and ‐7. Issue 1 (3rd September 2019) - Komaroff, Anthony L.; Zerr, Danielle M.; Flamand, Louis
Abstract: The 11th International Conference on Human Herpesviruses (HHV)‐6A, ‐6B, and ‐7 was held in Quebec City, from 23 to 26 June 2019. It attracted 144 basic, translational, and clinical scientists from 20 countries. Important new information was presented regarding: the mechanisms of chromosomal integration for HHV‐6A and ‐6B; the biology of inherited chromosomally integrated HHV‐6A and ‐6B; animal models for, and animal viruses with similarities to, HHV‐6A, ‐6B, and ‐7; established and possible disease associations, including provocative new information suggesting these viruses may be one trigger of Alzheimer's disease, and new treatment strategies. In this review, we summarize presentations that were of particular interest. The full text of the Abstracts cited in the manuscript is available in the online Supporting Information Materials.